Levoglucosenone: Bio-Based Platform for Drug Discovery - Camp, Jason E.; Greatrex, Ben W. (Frontiers in Chemistry, 2022)
Levoglucosone (LGO) is a bio-privileged molecule that can be produced on scale from waste biomass. This chiral building block has been converted via well-established chemical processes into previously difficult-to-synthesize building blocks such as enantiopure butenolides, dihydropyrans, substituted cyclopropanes, deoxy-sugars and ribonolactones. LGO is an excellent starting material for the synthesis of biologically active compounds, including those which have anti-cancer, anti-microbial or anti-inflammatory activity. This review will cover the conversion of LGO to biologically active compounds as well as provide future research directions related to this platform molecule.